THE ISSUES OF IMPLEMENTING THE RIGHT ACCESS TO JUSTICE FOR PEOPLE WITH DISABILITIES - Mutiah Wenda Juniar; Arini Nur Annisa; Nanda Yuniza; Andi Dahsyat (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
This research aims to find out what are the issues of implementing right access to justice in Indonesia and what are the possible solution to overcome the issues. This research used normative and doctrinal research method. The collection of legal materials was conducted by using literature and field research. The results of this research find out that there are at least four issues in implementing access to justice for people with disabilities in Indonesia. The issues are limited access to information regarding right access to justice; physical barriers; limited access to information regarding right access to justice and; lack of support and accommodation. Possible solution to overcome those issues such as providing regular training for legal enforcement regarding treatment for persons with disability, adjusting infrastructure to be accessible for persons with disabilities, utilizing technology to ease communication in all accessible format and providing services and reasonable accommodation based on personal assessment for persons with disabilities who are encountering legal cases.